Therapeutic study on Bacterial Respiratory Disease in Buffalo Calves - Raju Puppala, Sandeep; Rao Velamala, Vaikunta; Rani Nalluri, Lakshmi; Manda, Srinivas (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The cultural isolation and identification of nasal discharges from calves with respiratory disease revealed Pasteurella spp., E. coli, Streptococci spp., Klebsiella spp., Staphylococci spp. and Pseudomonas spp. The Pasteurella spp. was also identified from blood smears of clinical cases. The most predominant clinical signs observed were anorexia, pyrexia, depression, nasal and ocular discharges, congested conjunctival mucous membrane, cough and open mouth breathing. The prominent physical examination findings were tachypnoea, tachycardia, crackles, wheezes and dyspnoea. Haematological study showed anaemia, leukocytosis with neutrophilia and lymphopenia. Serum biochemical parameters showed hike in ALT, ALP, TP and fall in albumin. Thoracic radiography revealed consolidation of lungs. Therapeutic efficacy was proved to be superior in buffalo calves treated with Ceftiofur sodium when compared to Cefoperazone. Combination of Ceftiofur sodium, Meloxicam and Chlorpheneramine maleate was found to be effective for the treatment of bacterial respiratory disease in buffalo calves caused by Pasteurella spp.